Defenders of the Denial of the Armenian Genocide - Tunyan, Valery (History and Culture, 2021)
Individuals make a noteworthy contribution to Turkey's policy of denial of the Armenian Genocide. M. Perincek is distinguished by his activities regarding this issue. A feature of his activities is the promotion of the Eurasian Union between the Russian Federation, Turkey and Azerbaijan to resist Western influence, weaken the role of the Armenian factor, which will allow the Turkic countries to participate actively in the modernization process.
Keywords: Armenian genocide; politics of Turkey; biased historians; neo-Eurasianizm; confrontation; modernization; alliances